PENGARUH KUALITAS KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN (Studi Kasus BPJS Ketenagakerjaan Wilayah Sumbariau) - Lukito, Muhammad Pandu; Zulfadil, Zulfadil; Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to determine and analyze, the influence of leadershipquality and organizational culture on job satisfaction and its impact on employeeperformance on employee BPJS Employment Region Sumbariau. The researchmethod is explanatory research, where variables are measured by numericalscale, data collecting method using interview, with questionnaire. Dataprocessing using SPSS v18 software, with descriptive analysis and hypothesistesting path analysis. The results showed that (1) the quality of leadership had adirect and indirect effect through job satisfaction on employee performance onemployee BPJS Employment Region Sumbariau. (2) Organizational culture hasno direct effect on employee performance, but indirectly influence through jobsatisfaction on employee performance. this is caused by the dimensions ofAutonomy and Entrepreneurship seen from the distribution of respondents answerthis research (3) job satisfaction has a direct effect on employee performance andjob satisfaction variables which become intervening variable in this researchmediate the quality of leadership and organizational culture, increased if thequality of leadership and organizational culture first through job satisfaction.